A Novel Method for Assessing Cerebral Edema, Infarcted Zone and Blood-Brain Barrier Breakdown in a Single Post-stroke Rodent Brain - Kuts, Ruslan; Frank, Dmitry; Gruenbaum, Benjamin F.; Grinshpun, Julia; Melamed, Israel; Knyazer, Boris; Tarabrin, Oleg; Zvenigorodsky, Vladislav; Shelef, Ilan; Zlotnik, Alexander; Boyko, Matthew (Frontiers in Neuroscience, 2019)
Stroke is a major cause of global morbidity and mortality. Middle cerebral artery occlusion (MCAO) has historically been the most common animal model of simulating ischemic stroke. The extent of neurological injury after MCAO is typically measured by cerebral edema, infarct zone, and blood-brain barrier (BBB) permeability. A significant limitation of these methods is that separate sets of brains must be used for each measurement. Here we examine an alternative method of measuring cerebral edema, infarct zone and BBB permeability following MCAO in the same set of brain samples. Ninety-six rats were randomly divided into 3 experimental groups. Group 1 (n = 27) was used for the evaluation of infarct zone and brain edema in rats post-MCAO (n = 17) vs sham-operated controls (n = 10). Group 2 (n = 27) was used for the evaluation of BBB breakdown in rats post-MCAO (n = 15) vs sham-operated controls (n = 10). In group 3 (n = 42), all three parameters were measured in the same set of brain slices in rats post-MCAO (n = 26) vs sham-operated controls (n = 16). The effect of Evans blue on the accuracy of measuring infarct zone by 2,3,5-triphenyltetrazolium chloride (TTC) staining was determined by measuring infarct zone with and without an applied blue filter. The effects of various concentrations of TTC (0%, 0.05%, 0.35%, 0.5%, 1% and 2%) on the accuracy of measuring BBB permeability was also assessed. There was an increase in infarct volume (p<0.01), brain edema (p<0.01) and BBB breakdown (p<0.01) in rats following MCAO compared to sham-operated controls, whether measured separately or together in the same set of brain samples. Evans blue had an effect on measuring infarct volume that was minimized by the application of a blue filter on scanned brain slices. There was no difference in the Evans blue extravasation index for the brain tissue samples without TTC compared to brain tissue samples incubated in TTC. Our results demonstrate that measuring cerebral edema, infarct zone and BBB permeability following MCAO can accurately be measured in the same set of brain samples.